2003
DOI: 10.1113/eph8802626
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia Stimulates Aquaporin 1 Expression in the Fetal Sheep Heart

Abstract: Interstitial fluid fluxes are much greater in the fetus than in the adult, and filtration rates are increased over control in most tissues of the anaemic fetus. Increased capillary filtration may lead to cardiac oedema which, in turn, severely impacts cardiac function. Mechanisms that underlie these differences in flux are incompletely understood. One possible mechanism is an increase in capillary water permeability. Therefore, the goal of our study was to determine the level of expression of the water channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It has been hypothesized that the transmembrane ion current of myocardial cells, mediated by AQP1, requires rapid equilibrium of internal and external osmotic pressure (21,22). In a previous report, it was demonstrated that AQP1 expression was increased in anemic fetuses compared to agematched controls, suggesting that AQP1 plays an important role in physiological accommodation to fetal anemia (23). In this study, left ventricular mRNA and protein expression levels of AQP1 were measured following CPB surgery and the water content of myocardial muscle was determined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the transmembrane ion current of myocardial cells, mediated by AQP1, requires rapid equilibrium of internal and external osmotic pressure (21,22). In a previous report, it was demonstrated that AQP1 expression was increased in anemic fetuses compared to agematched controls, suggesting that AQP1 plays an important role in physiological accommodation to fetal anemia (23). In this study, left ventricular mRNA and protein expression levels of AQP1 were measured following CPB surgery and the water content of myocardial muscle was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Later in gestation one report suggested that total cardiac AQP1 levels reflected predominantly vascular sites, and that the total amount could be increased by fetal anemia [84]. …”
Section: Aquaporins In the Heart – Changes With Intrauterine Growth Rmentioning
confidence: 99%
“…At present, 13 types of AQP proteins (AQP-0-AQP-12) have been identified in mammals ( 7 ). AQP-1 is concentrated in microvascular endothelial cells and cardiomyocytes in myocardium ( 8 ). Furthermore, AQP-1 is highly expressed in cardiomyocytes and vascular endothelial cells in rabbits with chronic myocardial ischemia ( 9 ).…”
Section: Introductionmentioning
confidence: 99%